Impact of multicultural environment of Islamic educational institutes on students’ acculturation - Rahath House, Yousef; Abdul Razak, Mohd. Abbas (2016)
The study focuses on the effect of exposure to Multicultural and international environment of an Islamic educational institution on the acculturation of its students. Acculturation has been used in this study with a wide sense of meaning that underscores the sense of co-existence and feeling of unity. The analysis puts forth many studies that show the positive effects of intergroup contact between groups of diverse ethnic backgrounds and cultural heritages in reducing prejudice and negative stereotyping towards the out-group. This study investigated whether the Internationalization process of the International Islamic University, Malaysia, with intergroup contact taking place under optimal conditions helps its students to, appreciate the differences that other cultures bring, be comfortable with differences and also seek diversity of contact. The study employed Miville-Guzman Universality – Diversity Scale, (M-GUDS-S) to collect data by survey method from 400 IIUM undergraduate students selected using Quota sampling. 200 of them were the first year students and the rest were fourth-year students. The result showed that there is a significant improvement in the feeling of unity among the students. The fourth year students showed more appreciation for other cultures and comfort with differences. Based on the finding it has been suggested that if efforts are made to establish optimal conditions for positive intergroup contact to take place, intergroup prejudice can be reduced and problems of co-existence in the Muslim countries and communities can thus be addressed.